Model Pilihan Pembelajaran, Inquiry atau Expository? - Jumaisa Jumaisa (Jurnal Ilmiah Mandala Education (JIME), 2020)
There is no one the best learnings model compared to the other model. A learning model can be effective when it has reached the established goal. This research aims at providing the choice of learning models , whether inquiry or expository. The type of this research was literature by synthesize the literature data and previous studies. In the inquiry model, students are mentally and physically involved in solving the problem provided by the teachers, whereas the expository model, it emphasizes more on the way of speaking of teachers in delivering the material of subject